Dinamika Perubahan Paradigma Pendidikan: Studi tentang Kesiapan Guru Pendidikan Agama Islam di SD/MI di Wilayah Kabupaten Banyumas dalam Menerapkan Pendekatan Pembelajaran Saintifik dan Penilaian Otentik Kurikulum 2013 - Suparjo Suparjo (IAIN Purwokerto, 2014)
Abstract: This study was aimed at explaining the changes of educationparadigm among islamic education teachers in elementary schools and islamicelementary schools in Banyumas Regency, shown by teacher’s readiness inimplementing Curriculum 2013, especially in applying scientific method andauthentic assessment. This research used mixed methods, quantitative andqualitative methods. The research found that Islamic education teachers in bothgeneral and islamic elementary schools are ready to implement Curriculum 2013.In addition, they are also ready apply and develop scientific learning model andauthentic assessment as well as adapt to the new education paradigm. However,because of the lack of socialization, training, and facilities, they get some difficultiesin mastering knowledge about the curriculum and its implementation. From theresearch findings, it can be concluded that curriculum can be a starting point tochange the paradigm and practices of education as far as it is prepared and facilitated.Keywords: education paradigm, teacher, religious education, curriculum 2013. Abstrak: Hasil penelitian ini adalah bahwa guru PAI di SD maupun guru MI sudahsiap mengimplementasikan Kurikulum 2013, merasa mampu menerapkannyadalam mengembangkan model pembelajaran saintifik, penilaian otentik dan menyesuaikannyadengan paradigma baru pendidikan. Hanya saja, karena sosialisasidan pelatihan serta instrumen pendukung kurikulum belum tersedia secara makismal.Karenanya, mereka mengalami kendala dalam pengetahuan dan kemampuanmengimplementasikannya. Berdasarkan temuan tersebut dapat diambil kesimpulanbesar yakni, kurikulum mampu menjadi titik awal mengubah paradigmadan praktik pendidikan sesuai tuntutan idealisme pendidikan itu sendiri sejauhdilakukan persiapan dan fasilitas pendukung yang memadai.Kata Kunci: paradigma pendidikan, guru, pendidikan agama, dan kurikulum2013